Reading the "Paradoxical Book of Bell": a case study in theology and science - Penberthy, Joanna Susan (2019)
John Bell’s 1964 paper, “On the Einstein Podolsky Rosen Paradox,” written to explore Einstein’s contention that quantum theory is incomplete, has been cited extensively by theologians to support the contention that the quantum world evidences supraluminal connections. It is the centrepiece of Kirk Wegter-McNelly’s The Entangled God: Divine Relationality and Quantum Physics. Bell’s paper has been the focus of continuous research in theoretical and experimental physics since its publication in 1964 but while theologians overwhelmingly interpret Bell’s paper to support the nonlocality of the quantum world, the meanings drawn by quantum physicists and philosophers of science from the results of the experiments done to test the mathematical expression that lies at the paper’s heart are varied and contradictory. I explore the content, context and usages of Bell’s paper, showing how complex the making of scientific meaning is. I outline the multifarious interpretations of Bell’s paper by physicists, philosophers of science and theologians demonstrating that the various conclusions drawn from the experimental violations of his inequality, by those who believe them significant, whilst being cogent, rational and based upon scientific considerations, are not scientifically mandated but follow from the starting philosophical assumptions of physicists and philosophers of science and/or from the preconceptions they hold about the nature of science. I contend that interpretations of Bell’s paper will be thus inevitably multiple and that this epistemological plurality is both inescapable and irreducible. I show that while the final answer to what the experimental violations mean remains elusive this does not hinder their technological fruitfulness. I suggest philosophical and theological resources by which the fact of this potent epistemological multiplicity, seen theologically as a sign of our situatedness and creaturehood, can be explored rather than resisted. I note that Philip Clayton’s “tracing of lines” and Bernard d’Espagnat’s “fabricated ontology” offer conceptual possibilities in this regard.